Towards more culturally inclusive domestic toilet facilities in Australia - Othman, Zulkeplee; Buys, Laurie (Frontiers of architectural research, 2016)
The topics on toilets, defecation and perianal cleansing may be perceived as taboo subjects in daily discussions but are markedly important from health and hygienical perspectives. In multicultural countries like Australia, no research attention has been given to domestic toilet hygienical requirements from the perspective of the society＇s cultural traditions or religious teachings. The Western sitting lavatories with toilet paper facilities are the most common toilet systems available in Australian homes, which may be contradictory to persons coming from non- Western backgrounds. Squat latrines used widely in many Asian countries are acknowledged to be more conducive for maintaining a healthy bowel system, but are unattractive to Westerners and also unsuitable for those with physical disabilities. Similarly, water is regarded as the most hygienica[ option for perianal cleansing in many cultures but is rarely used in Western cultures. This paper investigates the experiences of seven Muslim families living in Brisbane with respect to whether or not the Australian toilet systems in their homes meet their personal and familial requirements. This paper further explores whether modifications were made to their domestic toilets to meet these essential needs. Some design recommendations are presented, which are based on the extant literature on this topic as well as the findings from this study. These design options provide an opportunity for future research focussed on a universal toilet design solution that is adaptable and able to meet the needs of all users, especially for those countries with a multicultural PoPulation.